1965
DOI: 10.1099/00221287-40-2-199
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NaCl in the Lysis of Staphylococcus aureus by Lysostaphin

Abstract: SUMMARYLysostaphin attacked both viable staphylococci and the mucopeptide portion of the staphylococcal cell wall. In the absence of salts, lysostaphin activity could only be recovered from the particulate portion of the lysed cell after centrifugation, whereas in the absence of salts its action on the mucopeptide resulted in a recovery of active material in both the sediment and the supernatant fluid. It appears from these observations that lysostaphin is complexed with its substrate and that NaCl is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1966
1966
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…These results suggest that the presence of ions in the enzymatic reaction environment inhibits the activity of the catalytic domains, and it seems that the CBD helps to overcome this limitation since the mature lysostaphin showed a notorious activity under physiological conditions. The regulation of lysostaphin activity by NaCl has been noticed shortly after discovery of this enzyme, 44 , 45 but it has never been properly investigated. Lu et al reported inhibitory effect of NaCl on the activity of lysostaphin and its enzymatically active domain, but the effect on isolated domain was much stronger.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the presence of ions in the enzymatic reaction environment inhibits the activity of the catalytic domains, and it seems that the CBD helps to overcome this limitation since the mature lysostaphin showed a notorious activity under physiological conditions. The regulation of lysostaphin activity by NaCl has been noticed shortly after discovery of this enzyme, 44 , 45 but it has never been properly investigated. Lu et al reported inhibitory effect of NaCl on the activity of lysostaphin and its enzymatically active domain, but the effect on isolated domain was much stronger.…”
Section: Resultsmentioning
confidence: 99%
“…Although this probably contributes to the ditferences observed, it is unlikely to be of great significance in view of the results of Virgilio et al (10), whose studies showed no comparable structural changes when S. aureus cell walls and mucopeptide were digested with lysozyme. Moreover, when S. au-reus cell wall mucopeptide was digested with lysostaphin, the whole structure appeared to be attacked at similar rates, and no structural differentiation was observed (9).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-associated a-toxin was released by lysis with lysostaphin, according to Schindler [9]; when lysis was complete, lysates were centrifuged at 7500×g at 5°C for 30 min.…”
Section: Starvationmentioning
confidence: 99%